A brief research report on the efficacy of a RAN training in elementary school age children - Wolfsperger, Joana; Mayer, Andreas (Frontiers in Education, 2024)
Numerous studies could prove that children with reading disorders show RAN deficits and that RAN is especially strongly connected to the automatization of word recognition. In contrast intervention studies so far have provided little convincing evidence for the trainability of RAN or even a transfer effect on reading competence. The aim of this study is therefore to evaluate the efficacy of an adaptive, software-based RANtraining in a group of 57 children aged 9;3 years (SD 1;10 years) with a RAN-Deficit and/or difficulties with word-reading-speed and to determine if there is a transfer effect to reading speed of words and pseudowords as well as to reading comprehension on the word-, sentence and text level. The software-based training of RAN letters, numbers and colors is an intervention over 18 training days. Children were encouraged to name visually presented items in a serial format as fast as a red rectangle jumping from item to item. The speed of the red rectangle was successively increased with each successful training session. Univariate ANOVAs with repeated measures showed that children had a significantly higher naming speed for letters and numbers both immediately after completion of the intervention and in the follow-up measures. A transfer of the training effect to reading speed for words, reading comprehension on the word-and sentence-level, but not to reading speed for pseudowords and text comprehension, could be demonstrated. Due to the missing of a control-group comparison, it remains to be proven in subsequent research whether this effect is a maturation-related change or a training effect.